Low flow analysis for drought management / Ismail Atan, Jurina Jaafar and Aminuddin Mohd Baki - Atan, Ismail; Jaafar, Jurina; Mohd Baki, Aminuddin (Institute of Research, Development and Commercialisation (IRDC), 2007)
A statistical method to fit the lower tail of the cumulative distribution function of streamflow is presented. The proposed model is distribution-free that is it does not require the specification of a parent distribution. The potential use of the proposed model is its ability to estimate small quantities of low flow distribution for drought management. The accurate estimation of low flow is very important for water resources planning and to illustrate the applicability of this model, the Langat River was selected.